2020
DOI: 10.3390/ijerph17217749
|View full text |Cite
|
Sign up to set email alerts
|

Which Occupation is Highly Associated with Cognitive Impairment? A Gender-Specific Longitudinal Study of Paid and Unpaid Occupations in South Korea

Abstract: Background: To examine the associations between paid and unpaid occupations and the risk of cognitive impairment with respect to gender in a middle-aged population using the dataset of a nationally representative longitudinal survey. Methods: Overall, 24,925 observations of 5865 participants aged 45–64 years were sampled from the seven waves of the Korean Longitudinal Study of Ageing (2006–2018). A dichotomous outcome variable was derived based on the Korean version of the Mini-Mental State Examination scores,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 74 publications
(113 reference statements)
0
12
0
2
Order By: Relevance
“…The Korean Longitudinal Study of Ageing showed that middle aged, full time homemakers had five times the risk of cognitive impairments compared with women in other occupations. 15 Furthermore, providing long term or high intensity care for a sick or elderly relative has been associated with an excess of psychiatric morbidity in women (eg, depression, anxiety, and lower life satisfaction). 16 Analysis of three waves of the UK Household Longitudinal Study to compare employment, earnings, and health effects in young people providing unpaid care found that young unpaid care givers for elderly, sick, and disabled people were mostly women, uneducated, living with a partner, and living in social housing.…”
Section: Unpaid Work Stress and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The Korean Longitudinal Study of Ageing showed that middle aged, full time homemakers had five times the risk of cognitive impairments compared with women in other occupations. 15 Furthermore, providing long term or high intensity care for a sick or elderly relative has been associated with an excess of psychiatric morbidity in women (eg, depression, anxiety, and lower life satisfaction). 16 Analysis of three waves of the UK Household Longitudinal Study to compare employment, earnings, and health effects in young people providing unpaid care found that young unpaid care givers for elderly, sick, and disabled people were mostly women, uneducated, living with a partner, and living in social housing.…”
Section: Unpaid Work Stress and Mental Healthmentioning
confidence: 99%
“…Unpaid work also has other unfavourable deleterious effects. The Korean Longitudinal Study of Ageing (2006–18) showed that middle aged, full time homemakers had five times the risk of cognitive impairments compared with women in other occupations 15…”
Section: Unpaid Work Stress and Mental Healthmentioning
confidence: 99%
“…The analysis of 2347 individuals from the Doetinchem Cohort Study revealed that an unhealthy lifestyle and relatively poor health in midlife were significantly associated with worsened cognition 10 years later, regardless of gender or educational level [ 25 ]. Unfortunately, the small sample size was limited, and occupation, although important, was not assessed as a possible risk factor for cognitive impairment [ 28 , 29 ]. Subsequently, the testing of visuospatial working memory performance among 134 individuals between 20 and 80 years of age in Italy revealed that educational level was positively associated with working memory performance.…”
Section: Introductionmentioning
confidence: 99%
“…Also, our study found no sig nif i cant re la tion ship be tween sociodemographic fac tors and cog ni tive func tions. A study by W. Chung et al showed that mid dle-aged fe male home mak ers were found to have a 5-fold higher risk of cog ni tive fail ures than working fe males [56]. Also, cog ni tive de cline was found to be slower in those with higher ed u ca tion than among those with no ed u ca tion [57].…”
Section: Discussionmentioning
confidence: 99%